Morphometric variations in the reef crab Plagusia depressa (Decapoda: Plagusiidae) in the Western tropical Atlantic - Costa, Anne Karolline; Albuquerque Lira, Simone Maria; Nunes Silva, Lucas; Schwamborn , Ralf (Revista de Biología Tropical, 2024)
Introduction: The reef crab Plagusia depressa is widely distributed in tropical oceans. In the Atlantic Ocean, this species is distributed in geographically distant regions with different environmental pressures, which may lead to morphological divergence. Objectives: To explore morphometric differences in Plagusia depressa populations between coastal reefs and an oceanic island in the Western tropical Atlantic. Also, to examine the potential link between the species’ phenotypic plasticity and environmental and geographic factors. Methods: A total of 194 crabs were sampled from four Brazilian coastal and oceanic sites (Suape: n= 52, Tamandaré: n= 53, Barra Grande: n= 44, and Fernando de Noronha Archipelago: n= 45) from 2020 to 2022, under distinct anthropogenic and environmental influences. Linear and geometric morphometric analysis employed seven linear measurements and specific landmarks on the carapace, abdomen, and right chelae to pinpoint significant morphometric differences among these areas. Results: The westernmost coastal population exhibited striking differences from the other regions. Male crabs in this population had a pronounced carapace rostrum, while females showed a narrower abdomen, longer telson, and chelae thinning and elongation. It is possible that the pronounced isolation in this area, along with patterns of changes in ocean currents, may influence our results. Female crab carapaces from the island area showed lateral enlargement and pronounced rostrum depressions. Furthermore, being farther from the mainland, this site has oceanic island environmental features, affecting the population through desiccation and air exposure. For male crabs, different right chelae shape across areas showed an impact of food capture and interaction with other organisms on their phenotypic plasticity. Conclusion: Environmental factors such as tidal exposure and habitat composition might affect the phenotypic plasticity of tidal crabs. Moreover, a biogeographical barrier in Northeastern Brazil, which was hitherto given little consideration, holds important implications for the biogeography of the Western tropical Atlantic.